PSYCHOLOGICAL FEATURES OF THE DEVELOPMENT OF MANAGEMENT COMPETENCIES OF STUDENTS (American Journal of Research in Humanities and Social Sciences, 2023)
This article covers the characteristics of the development of student management competencies, the fact that a competency-based approach in education involves ideas of professional and general, intellectual development, and forms of interdependence and metasubject, which embody correlations.